Analysis of Drug Procurement Results in Vietnam from 2013 to 2020 - Thi Hai Yen, Nguyen; Hiep, Phung The; Thi My Dung, Nguyen; Danh, Le Ngoc; Ngan, Thai Hue; Nguyen, Le Dang Tu (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 39 No 1DO - 10.25073/2588-1132/vnumps.4387, 2023)
Abstract: Drug procurement bidding has always been under the government’s particular concern to assure drug quality, stabilize drug costs, and enhance the use of domestic drugs. A retrospective study analyzes data from the drug procurement results in Vietnam from 2013 to 2020 based on the results reported to the Drug Administration of Vietnam. The rate of drugs selected through the bidding process in Hanoi and HCMC accounted for the highest proportion in the country with 17.5% and 14.3%, respectively. The number of selected drugs with domestic origins had seen a gradual increase over the years with 4545 drugs during 2020, which was 2.2 times higher than that of 2013 (2079 drugs). Generic drugs in group 3 with domestic origins comprised the highest proportion of both quantity and value compared to drugs in other groups. Antiparasitic drugs and anti-infectives had the highest value rates among pharmacological groups with over 20%. During the research period, the costs of selected drugs tended to witness a decreasing trend, accounting for 60% of drugs. Only 9% of the drugs had their values remain unchanged, and the other 31% saw an increase in these values. State bidding procurement policies are making positive effects in lowering drug costs and encouraging domestic drug use. However, the value rate of domestic drugs is still lower than that of imported ones. It is necessary for domestic pharmaceutical enterprises to invest in developing factories, actively find domestic ingredient sources, and focus on specific medications in great demand. Keywords: Drug bidding, drug price, generic bidding package, original brand name bidding package, period of 2013-2020, Vietnam.